2009
DOI: 10.1525/auk.2009.07181
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Demands During Incubation and Chick Rearing in a Uniparental and a Biparental Shorebird Breeding in the High Arctic

Abstract: Abstract.-Rearing of young has long been considered the energetically most demanding phase of the avian breeding cycle. Arctic-breeding shorebirds expend large amounts of energy during breeding. Because they are too small to carry sufficient stores to sit out the incubation period, they regularly interrupt incubation to feed and still can run short of energy, particularly in species in which one adult takes care of the eggs and chicks alone (uniparental). We measured daily energy expenditure (DEE) and time bud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 31 publications
2
25
0
1
Order By: Relevance
“…Though laboratory studies have indicated that younger chicks may be highly vulnerable to impacts of temperature and food availability19, our results indicate that the behaviour of brooding adults appears to diminish this impact in the wild, at least for chicks less than 5 days old. As adults tend to brood young for longer periods of time as ambient temperatures decrease22, increases in temperature during the brood rearing season could also have the potential to alleviate costs of parental care, especially for uniparental species for which these costs are particularly high23.…”
Section: Discussionmentioning
confidence: 99%
“…Though laboratory studies have indicated that younger chicks may be highly vulnerable to impacts of temperature and food availability19, our results indicate that the behaviour of brooding adults appears to diminish this impact in the wild, at least for chicks less than 5 days old. As adults tend to brood young for longer periods of time as ambient temperatures decrease22, increases in temperature during the brood rearing season could also have the potential to alleviate costs of parental care, especially for uniparental species for which these costs are particularly high23.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there may be three reasons why this assumption is not supported at my study site. First, if prey availability was very limited then males should not have been able to gain body mass during incubation, especially considering that breeding male Dunlins have substantially higher energetic costs than breeding females (> 25% higher daily energy expenditure; Tulp et al 2009). There is also no reason why males should be more successful foragers than females, or that they are able to spend more time foraging.…”
Section: Discussionmentioning
confidence: 99%
“…For example, ambient temperature (T a ) influences the percentage of time female little stints (Calidris minuta) spend brooding and foraging (i.e. females brood more when T a is low) (Tulp et al, 2009). To reduce egg desiccation, female prairie skinks (Eumeces septentrionalis) increase their egg-brooding behaviors when the nest substrate is relatively dry (Somma and Fawcett, 1989).…”
Section: Discussionmentioning
confidence: 99%